A multisector community-engaged collaborative for mental health integration in primary care and housing developments: Protocol for a stepped-wedge randomized controlled trial (the Harlem Strong Program) - Victoria K. Ngo; Thinh T. Vu; Deborah Levine; Malcolm A. Punter; Susan J. Beane; Marina R. Weiss; Katarzyna Wyka; Jose F. Florez-Arango; Xin Zhou (BMC, 2024)
Abstract Background Addressing mental health disparities following COVID-19 requires adaptive, multi-sectoral, equity-focused, and community-based approaches. Mental health task-sharing in gateway settings has been found to address mental health care gaps in low- and middle-income countries, but is not a common practice in the U.S., especially in non-medical settings, such as low-income housing developments (LIH). This research study will evaluate the effectiveness of a multisectoral community-engaged collaborative for task-sharing mental health care on consumer, provider, and implementation outcomes, as well as identify barriers and facilitators for implementation. Methods In this stepped-wedge randomized controlled trial with technology supplementation, LIH and primary care sites will be randomly assigned to one of five sequences of three implementation strategies: (1) Education and Resources (E&R), which involves online training and resources on basic mental health task-sharing skills, (2) Multisectoral Community Collaborative Care (MCC), which consists of all E&R resources plus additional community responsive implementation supports and participation in a multisectoral coalition and (3) MCC + Technology, which combines the MCC condition resources with a community crowdsourced technology solution to support implementation. The primary outcome is the effectiveness in meeting consumers' needs through direct service (e.g., adequately addressing depression and anxiety symptoms), and through implementation to increase access to mental health care (reach). The secondary outcome examines additional consumer outcomes including health functioning and social risks, as well as implementation outcomes including provider skills, program adoption, and factors related to barriers and facilitators of quality implementation. A total of 700 consumers receiving mental health care at 20 sites will be surveyed at baseline, 6-, and 12-month follow-ups. Additionally, 100 providers will be evaluated at baseline, 6-, 12-, and 24-month follow-ups before training and after randomization. Discussion We hypothesize that MCC and MCC + Technology conditions will demonstrate significantly higher efficacy in changing primary outcomes compared to E&R, and the MCC + Technology supplement will show significantly higher levels of reach of mental health tasks compared to the MCC condition alone. These findings will demonstrate the feasibility of mental health integration into accessible, non-medical community settings such as LIH. Moreover, it will help establish a multilevel system solution based on community engagement and planning with a multisectoral collaboration that can be sustained community-wide. Trial registration NCT05833555 on Clinicaltrials.gov. Registered April 26, 2023